Process optimisation: spinal versus general anaesthesia for endourological surgery. A randomised, controlled trial and machine-learning approach - Kornel Skitek; Gregor A. Schittek; Jens Soukup (Anaesthesiology Intensive Therapy)
Introduction Data concerning anaesthesia for endourology are rare, and options for it are numerous. Thus, identifying the optimal anaesthesia regimen remains challenging. With this study we aimed to provide the means for selecting optimal anaesthesia for endourology procedures.